Doctoral Studies of Students in Educational Administration Programs in UCEA Member Institutions - M. Scott Norton; Frederick D. Levan (Educational Considerations, 1987)
This research shows that the Ph.D and Ed.D degree programs in educational administration are virtually identical pursuits in UCEA member institutions.